RETRACTED ARTICLE: Mycoplasmosis in poultry: update on diagnosis and preventive measures. Issue 1 (1st March 2017) - Umar, S.; Munir, M.T.; Ur-Rehman, Z.; Subhan, S.; Azam, T.; Shah, M.A.A.
Abstract : We, the Editor and Publisher of World's Poultry Science Journal, have retracted the following article: S. Umar, M.T. Munir, Z. Ur-Rehman, S. Subhan, T. Azam & M.A.A. Shah, 'Mycoplasmosis in poultry: update on diagnosis and preventive measures' (2017) 73:1, 17-28 https://doi.org/10.1017/S0043933916000830 . The above article has been retracted as, subsequent to publication, significant duplication has been found in content throughout the article, particularly in the 'Abstract, ' 'Introduction, ' 'Medication, ' 'Vaccination, ' 'Diagnosis' and 'Conclusion' with the following published works; Kleven, S.H. 'Control of Avian Mycoplasma Infections in Commercial Poultry' Avian Diseases (2008) 52(3), 367-374 DOI 10.1637/8323-041808-Review.1 Nascimento, ER; Pereira, VLA; Nascimento, MGF; and Barreto, ML. Avian mycoplasmosis update. Brazilian Journal of Poultry Science (2005), 7:1 DOI 10.1590/S1516-635X2005000100001 We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted". © 2020 Informa UK Limited, trading as Taylor & Francis Group